Laurobasidium hachijoense, comb. nov. (Cryptobasidiaceae) causing aerialroot-like galls on Cinnamomum japonicum in Japan - Kakishima, Makoto; Nagao, Hideyuki; Denchev, Cvetomir M. (Phytotaxa, 2017)
A new combination, Laurobasidium hachijoense, is proposed to accommodate Exobasidium hachijoense from Japan, producing aerialroot-like galls on stems of Cinnamomum japonicum. This combination is based on the presence of a gastroid-like sporulation on the surface of the galls, and is supported also by the host-plant specialization and molecular data.